Effect on Perceived Stimulation dan Perceived Crowding on the Decision of the Unplanned Purchase (Impulse Buying) - Sriwardiningsih, Enggal (Binus Business Review, 2011)
Purchase decisions arenât made necessarily planned, because impulsive buying is such a result of environmental stimuli shopping. Things affecting unplanned purchasing decisions are perceived by stimulation and crowding. The purpose of this study is to determine whether there are influences between perceived crowding and stimulation of impulse buying simultaneously or partial. The object used is one of the largest retailers in Cilegon. This research design is quantitative analysis of the consumer unit. The collecting data technique includes using questionnaires, interviews, and literature from previous research. Data processed using the SPSS 16.0 program through the validity and reliability, normality test, and regression analysis. The study states that there is significant influence between perceived crowding and perceived stimulation both simultaneous and partial response to impulse buying.Â